(untitled) (Archives of Mechanics - Test, 1997)
The aim of the paper is to provide a general and common mathematical structure for a class of orthotropic materials undergoing plastic deformations or exhibiting locking behaviour. The orthotropy is included by using a fabric tensor. The tensorial constitutive relationships are studied from the point of view of tensor functions representations. Specific cases are also discussed.